2019
DOI: 10.1080/01443410.2019.1699907
|View full text |Cite
|
Sign up to set email alerts
|

Civic knowledge and open classroom discussion: explaining tolerance of corruption among 8th-grade students in Latin America

Abstract: The endorsement of anti-corruption norms is a normative assumption in legal systems with freedom of information acts, where citizens are expected to act as monitors of the public service.Tolerance of corruption counteracts this assumption. We studied tolerance of corruption among 8th graders from Latin-American samples of the International Civic and Citizenship Study 2009.We proposed a model where associations between students' socioeconomic status (SES) and tolerance of corruption are explained by civic knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
10
0
3
Order By: Relevance
“…Thus, we expect a higher tolerance of corruption from more authoritarian students, under the assumption that corrupt acts are a particular example of unethical behaviors (Moore 2008;Nwabuzor 2005). Previous research, using data from ICCS 2009, has found this relation among grade 8 students from six Latin American countries (Carrasco et al 2020), where higher endorsement of authoritarianism is associated with higher tolerance of corruption. Thus, in the present study, we expect students with high endorsement of authoritarianism to present higher tolerance of corruption.…”
Section: Conceptual Backgroundmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, we expect a higher tolerance of corruption from more authoritarian students, under the assumption that corrupt acts are a particular example of unethical behaviors (Moore 2008;Nwabuzor 2005). Previous research, using data from ICCS 2009, has found this relation among grade 8 students from six Latin American countries (Carrasco et al 2020), where higher endorsement of authoritarianism is associated with higher tolerance of corruption. Thus, in the present study, we expect students with high endorsement of authoritarianism to present higher tolerance of corruption.…”
Section: Conceptual Backgroundmentioning
confidence: 83%
“…The endorsement of authoritarianism is another predictor of tolerance of corruption (Carrasco et al 2020). Authoritarianism is a tendency to support strong authorities (Altemeyer 1981), favoring uncritical obedience and respect for such authorities (Duckitt et al 2010).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, cuanto mayor es el nivel socioeconómico mayor es el conocimiento cívico, aunque, a diferencia de lo que ocurre con el género, la diferencia en el nivel socioeconómico se mantiene estable entre 2009 y 2016. Finalmente, otras variables ya relevadas por estudios anteriores, como el rol de la discusión en la sala de clases y fuera de la escuela (Carrasco, Banerjee, Treviño y Villalobos, 2020;Treviño et al, 2017) son estadísticamente significativos en ambos años, aunque con magnitudes similares. Las ILSA han sido motivo de un creciente debate académico durante la última década.…”
Section: Resultsunclassified
“…Carrasco et al (2020), Deimel et al (2020), and Knowles (2020) used this technique to examine the similarity and differences regarding factors in civic learning for alienated, disaffected or disadvantaged students across different countries, whereas Van Droogenbroeck and Spruyt (2020) examined the relationship between perceived social pressure for religious conformity and antigay sentiment on Christian and Muslim youth. Beyond these cross-group comparisons, Carrasco et al (2020) also constrained the parameters for the same pathway to be equal across countries and obtained a summary of the results across countries. This provides another method to summarise results across groups in addition to taking the mean of the results.…”
Section: Editorialmentioning
confidence: 99%